Downregulation of transforming growth factor, beta receptor 2 and Notch signaling pathway in human abdominal aortic aneurysm - Biros, Erik; Walker, Philip J.; Nataatmadja, Maria; West, Malcolm; Golledge, Jonathan (Atherosclerosis, 2012)
► Genetic resemblance between abdominal aortic aneurysm and Marfan syndrome. ► TGFBR2 is subject to acquired copy number variations that might contribute to the pathogenesis of abdominal aortic aneurysm. ► TGFBR2 haploinsufficiency in abdominal aortic aneurysm. Mutations in FBN1 and TGFBR2 genes are the main causative mutations identified in Marfan syndrome (MFS). The major vascular complication of MFS is aneurysm formation. Abdominal aortic aneurysm (AAA) is an acquired disease of later life of unknown etiology. The aim of this study was to examine if genetic aberrations in MFS-related genes FBN1 and TGFBR2 are present in patients with AAA. We assessed the presence of copy number variation (CNV) in FBN1 and TGFBR2 genes in AAA biopsies from twelve patients. We also analyzed the expression of these genes in AAA biopsies compared to control biopsies from six organ donors. In addition we assessed the expression of two members of the Notch signaling pathway NOTCH3 and HEY2 as well as aortic smooth muscle cell (AoSMC) differentiation marker TAGLN in AAA and control biopsies. Loss of one copy (deletion) of the FBN1 exon 66 sequence and TGFBR2 exon 8 was identified in 7 (58%) and 11 (92%) of the 12 AAA biopsies. No copy number amplifications (duplications) were detected. Patients carrying TGFBR2 exon 8 deletion showed marked downregulation of this gene in AAA biopsies compared to control biopsies (0.699 vs. 1.765, p=0.038). Notch signaling components NOTCH3 and HEY2 were markedly downregulated in AAA, while expression of the AoSMC differentiation marker TAGLN did not differ between AAA and control biopsies (0.468 vs. 0.486, p=0.546). This study suggests an acquired impairment in TGF-β signaling that along with downregulation of the Notch signaling pathway may contribute to the pathogenesis of AAA.